Evaluating Immediate and Short-Term Postoperative Clinical Outcomes of Patients Undergoing Ulnar Shortening for Ulnar Impaction Syndrome Using PROMIS - Bernstein, David N.; Lander, Richard D.; Hammert, Warren C. (Journal of Wrist Surgery, 2021)
Background The early recovery trajectory of patients undergoing ulnar shortening for ulnar impaction syndrome using the Patient-Reported Outcomes Measurement Information System (PROMIS) is unknown.Questions/Purposes Using PROMIS Upper Extremity (UE), Physical Function (PF), Pain Interference (PI), and Depression, we asked (1) do patients undergoing operative management for ulnar impaction syndrome present at their preoperative visit with notable impairment?; (2) At immediate follow-up, do patients present with a clinically appreciable change in symptom severity?; and (3) At short-term follow-up, do patients present with a clinically appreciable change in symptom severity?Materials and Methods We identified patients from 01/2017 to 12/2019 at our institution undergoing ulnar shortening for ulnar impaction syndrome who completed all PROMIS domains at a preoperative visit and at least one postoperative time point (i.e., less than 4 weeks and/or greater than 12 weeks). Distribution- and anchor-based minimal clinically important difference estimates were used to evaluate clinically appreciable changes in symptoms over time.Results A total of 38 patients met our inclusion criteria. The average change in PROMIS UE, PF, PI, and Depression scores from preoperative to immediate postoperative follow-up were –3.8, –4.3, 3.2, and 0.5, respectively. However, by short-term follow-up, the average change in PROMIS UE, PF, PI, and Depression scores were 3.7, 3.2, –4.7, and –3.9, respectively.Conclusions Patients have worsening function at the immediate postoperative follow-up. By short-term postoperative follow-up, functional status and PI levels improve. Our findings can help hand surgeons provide evidence-based guidance on expected initial recovery following operative management for ulnar impaction syndrome.Level of Evidence This is a level II, prognostic study.
Keywords: ulnar impaction syndrome; recovery pattern; patient-reported outcome measures; PROMs; PROMIS